Analysis of a long term starved Pseudomonas aeruginosa ATCC27853 in seawater microcosms. (September 2019) - Machreki, Yasmine; Kouidhi, Bochra; Machreki, Sawsen; Chaieb, Kamel; Sáenz, Yolanda
Abstract: The persistence of pathogenic bacteria in the marine environment has been thoroughly investigated. The potential threat that these microorganisms pose to public health in recreational waters has always been a concern. In this study, the persistence and the response of Pseudomonas aeruginosa ATCC27853 to starvation and osmotic stress were studied after its incubation in sterilized seawater during 12 months. Three different colonial variants were isolated: A7 after one month, and A81 and A82 after 8 months of incubation period. The incubation effect on the bacterial phenotype and genotype were studied by analyzing modifications in morphology, antibiotic and metal resistance, molecular typing (PFGE and MLST), pigment production and virulence factors. The starved variants showed three different colony forms, but an indistinguishable PFGE pattern and belonged to ST155, as P. aeruginosa ATCC27853. The starved variants maintained the susceptibility to the 13 tested antibiotics, with the exception of the imipenem-resistant A82 strain, which also showed a small colony variant phenotype and the highest values of tolerance to the CuSO4  + NaCl combination. Significant differences were detected in the pigment production, the elastase activity and cytotoxic potential of the starved isolates in comparison to P. aeruginosa ATCC27853. Long-term exposure to stress, such as the incubation in seawater, was shown to induce different responses in P. aeruginosa, including virulent and resistant phenotypes. Highlights: Culturability and physiological adaptation of P.aeruginosa ATCC27853 incubated in seawater for 12 months were investigated. The studied genomic parameters were conserved. The antibiotic resistance and the secretion levels of elastase, phenazines pyorubin and pyocianin were variable. Cytoxicity also varied between the studied variants and the non-incubated strain.